Violeta : a novel - Allende, Isabel (Ballantine Books, 2022)
"This sweeping novel from the New York Times bestselling author of A Long Petal of the Sea tells the epic story of Violeta Del Valle, a woman whose life spans one hundred years and bears witness to the greatest upheavals of the twentieth century"--